Study on The Use Of Experiment to Improve Software usability - Fathiah, Fathiah (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2015)
The use of experiment is a skill that is essential for practitioners and professionals whose sole purpose is to provide guidance for product developers to improve the ease o the f use of their products. Not that the science of testing is the only ability that must be owned by a professional, but knowledge about this very important. In addition, the use of experiment is a research tool, with its roots in the classical experimental methodologies. The range of tests that can be done fairly large, classic experiments with a large sample size and design of complex test or qualitative studies are very informal with only a single participant. Each testing approaches have different goals, and different time and resource requirements.Keyword: Usability, experiment, testing, research, design, requirement.